Shifting dynamics and environmental implications of the irrigation pump market in India - Chandra, Ankit; Brozović, Nicholas (Frontiers in Environmental Science, 2024)
• India is the world's largest user of groundwater for irrigation, with approximately 32 million pumps running on diesel, electric, and solar power.• Subsidized electricity has led to an increase in the adoption of electric pumps by farmers, with increasing electrification rates and rising diesel costs contributing to the trend.• Government subsidies have been instrumental in enhancing smallholder irrigation pump access. However, subsidies on irrigation pumps may exacerbate undesirable groundwater depletion.• In smallholder settings where the capital needed to purchase irrigation equipment exceeds farmers' means, "irrigation-as-a-service" and "rental pumps" with organized and affordable volumetric pricing could offer viable solutions.• This policy brief provides key learnings on the Indian irrigation pump market and its policy and environmental implications, based on semi-structured interviews and secondary data collected.